A birch ELONGATED HYPOCOTYL 5 gene enhances UV-B and drought tolerance - Shangzhu Gao; Xiaohui Chen; Meihan Lin; Yibo Yin; Xiaoyi Li; Yaguang Zhan; Ying Xin; Fansuo Zeng (Forestry Research)
UV-B radiation and drought majorly restrict plant growth, particularly in summer. ELONGATED HYPOCOTYL 5 (HY5), a bZIP transcription factor (TF), has a beneficial impact on photomorphogenesis. However, the sequence of HY5 from Betula platyphylla (BpHY5) has not been identified and the gene functions remain unclarified. We cloned the sequence of BpHY5, which was targeted to the nucleus. The hypocotyl phenotypes of heterologous expression in Arabidopsis thaliana and reverse mutation showed that BpHY5 is homologous to AtHY5. The expression of BpHY5 was increased in response to UV-B radiation, drought conditions, and the presence of abscisic acid (ABA). The overexpression of BpHY5 resulted in increased tolerance to UV-B radiation and drought and decreased ABA sensitivity with higher germination and greening rate, more developmental root system, stronger reactive oxygen species scavenging ability, and lower damage degree. The lignin content under UV-B condition of BpHY5/Col was higher than that of Col. Furthermore, overexpressing BpHY5 up-regulated the expression of genes related to tolerance (NCED3/9, ABI5, DREB2A, RD20, ERF4, NDB2, and APX2). In brief, the study suggests that BpHY5 from birch serves as a beneficial modulator of plant responses to UV-B radiation and drought stress.